Academic Writing Students’ Affective Reactions towards Joint Reconstruction Phase of Reading to Learn - Listyani Listyani (Soegijapranata Catholic University, 2017)
Academic Writing can be considered a difficult writing course which can make students exhausted and even frustrated. The principle of the more you read, the better you write may be applicable to this course. One way to make students write better is by asking them to read more and giving them some model texts to learn. Asking them to work collaboratively with their peer students can also help. The series of steps are included in Reading to Learn (R2L) teaching method that I developed for my Academic Writing Class in Semester II/ 2015-2016 Academic Year. This study mainly tried to describe how introverted and extroverted students of an Academic Writing class of the Faculty of Language and Literature, Universitas Kristen Satya Wacana Salatiga, Indonesia, reacted to the phase when they were supposed to work with their peers to produce an outline and an essay. Among other 21 students in the class, five who were found to be introverted, and five other extroverted, became the respondents of the study. They were selected based on questionnaires they filled in the previous semester. Data were mainly derived from journals that they submitted every time they passed a step, and also from observation done through video recording during the whole semester. Findings show that the ten students showed different affective reactions towards collaborative writing